Exploring the use of Smart Mobile Devices and their applications for infocommunication and Personal Knowledge Management in the personal lives of teachers - Oliveira, Dalbert; Terra, Ana Lúcia; Peres, Paula (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This article is part of a PhD research and investigates the impact of rapid technological evolution, focusing on the adoption of smart mobile devices (SMD), such as smartphones, tablets and laptops, and applications (app) in the personal lives of higher education professors in the area of Information Science. In addition, gaps are identified in existing research, emphasizing the need to understand how SMD is used in personal activities for personal knowledge management (PKM) practices and infocommunication. Specific objectives include identifying the most commonly used SMDs and apps, the frequency of such use, and how they are used for those practices. The methodology is qualitative, triangulating the integrative review with a questionnaire (N-10). The results point to interest in device ecologies for PKM and Info-communication, with communication apps (text and voice) and e-mail being the most important for teachers. It is hoped that the results of this study can contribute to the advancement of knowledge about the use of SMD by teachers and to the development of a generic descriptive model of infocommunicational behaviour and PKM that can be applied in other contexts.